2018
DOI: 10.3390/rs10091339
|View full text |Cite
|
Sign up to set email alerts
|

ERN: Edge Loss Reinforced Semantic Segmentation Network for Remote Sensing Images

Abstract: Abstract:The semantic segmentation of remote sensing images faces two major challenges: high inter-class similarity and interference from ubiquitous shadows. In order to address these issues, we develop a novel edge loss reinforced semantic segmentation network (ERN) that leverages the spatial boundary context to reduce the semantic ambiguity. The main contributions of this paper are as follows: (1) we propose a novel end-to-end semantic segmentation network for remote sensing, which involves multiple weighted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(40 citation statements)
references
References 53 publications
0
37
0
Order By: Relevance
“…Table 1 shows the classification results in terms of the per-class accuracy, the mean F 1 score, the mIoU, and the overall accuracy (OA) of experiments on the Vaihingen dataset. As a comparison, we also show the results recently published by SVL-boosting + CRF [54], RF + dCRF [55], RotEqNet [56], HSNet [19], and ENR [34] with a model of the same architecture and size as ours. It is demonstrated that REMSNet outperforms other methods in terms of the mean F 1 score, mIoU, and overall accuracy.…”
Section: Results and Analysismentioning
confidence: 91%
See 2 more Smart Citations
“…Table 1 shows the classification results in terms of the per-class accuracy, the mean F 1 score, the mIoU, and the overall accuracy (OA) of experiments on the Vaihingen dataset. As a comparison, we also show the results recently published by SVL-boosting + CRF [54], RF + dCRF [55], RotEqNet [56], HSNet [19], and ENR [34] with a model of the same architecture and size as ours. It is demonstrated that REMSNet outperforms other methods in terms of the mean F 1 score, mIoU, and overall accuracy.…”
Section: Results and Analysismentioning
confidence: 91%
“…To explicitly represent class boundaries, Marmanis et al [33] added boundary detection to the SegNet to further refine classification results. Liu et al [34] introduced multiple weighted edge supervisions based on the encoder-decoder framework to leverage the spatial boundary context and reduce the semantic ambiguity. Some work also uses multi-source data fusion data to reduce ambiguous boundary.…”
Section: Semantic Segmentation For High-resolution Aerial Imagesmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on previous studies [51][52][53]58,59], approximately 80% of the pixel-by-pixel classification results generated by CNN models are credible. Therefore, only approximately 20% of the pixel classification results require post-processing.…”
Section: Description Of the Modeling Schemementioning
confidence: 90%
“…RefineNet [52], form the basis for the rapidly developing field of remote sensing image segmentation. Although the use of CNNs can significantly improve the accuracy of remote sensing image segmentation, errors remain common near object edges owing to the inherent characteristics of the convolution operation [49][50][51]53]. Thus, convolution must be combined with other post-processing techniques to improve the accuracy of the results [51,54,55].…”
Section: Introductionmentioning
confidence: 99%